2011
DOI: 10.1002/gps.2516
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of memantine in PDD and DLB: an extension study including washout and open-label treatment

Abstract: The findings inform clinical practice that any possible memantine-associated benefits might be rapidly lost after drug withdrawal. The magnitude of deterioration suggests a symptomatic rather than a disease-modifying effect of the drug. Open-label results should merely be considered inspiration for future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 27 publications
1
18
0
1
Order By: Relevance
“…Perhaps this could indicate that patients can benefit from treatment with memantine, but only when it is introduced early in the clinical course. Furthermore, this is in line with the study on the same population by Johansson et al ,19 who noticed a global improvement in the placebo group as well as in the memantine group during the 30 weeks of open-label follow-up, but the change in CGIC was not significant.…”
Section: Discussionsupporting
confidence: 91%
“…Perhaps this could indicate that patients can benefit from treatment with memantine, but only when it is introduced early in the clinical course. Furthermore, this is in line with the study on the same population by Johansson et al ,19 who noticed a global improvement in the placebo group as well as in the memantine group during the 30 weeks of open-label follow-up, but the change in CGIC was not significant.…”
Section: Discussionsupporting
confidence: 91%
“…It is worth noting that the use of mitochondrially-directed antioxidants, calcium chelators/metal protein-binding compounds, NMDA receptor inhibitors, and caspase inhibitors have been developed but have demonstrated modest to no benefit in clinical trials for treating various brain degenerative disorders (Snow, et al 2010) (Johansson, et al 2011) (Bonelli, et al 2006) (Regland, et al 2001) (Sampson, et al 2012). The development of pharmacologically active compounds that can tout protective signaling in neurons poses a paramount challenge due to the compartmentalized nature of PKA signaling pathways in neurons.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 clinical trials evaluating the efficacy of interventions in PDD were identified . All of these trials assessed pharmacological treatments.…”
Section: Resultsmentioning
confidence: 99%